2016
DOI: 10.5194/hess-20-2691-2016
|View full text |Cite
|
Sign up to set email alerts
|

Contradictory hydrological impacts of afforestation in the humid tropics evidenced by long-term field monitoring and simulation modelling

Abstract: Abstract. The humid tropics are exposed to an unprecedented modernisation of agriculture involving rapid and mixed land-use changes with contrasted environmental impacts. Afforestation is often mentioned as an unambiguous solution for restoring ecosystem services and enhancing biodiversity. One consequence of afforestation is the alteration of streamflow variability which controls habitats, water resources, and flood risks. We demonstrate that afforestation by tree planting or by natural forest regeneration ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 44 publications
(61 reference statements)
1
48
1
Order By: Relevance
“…In the context of climate change, annual rainfall in South-East Asia is expected to increase [86]. However, combined to the expansion of higher evaporative demand perennial crops, groundwater recharge may decrease [87] and be less available for human needs. Concomitantly, more intense rainfall and land use changes towards annual crops or trees without understorey may increase runoff and decrease water travel times downstream, thereby reducing the filtration process of pathogens before entering the stream.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of climate change, annual rainfall in South-East Asia is expected to increase [86]. However, combined to the expansion of higher evaporative demand perennial crops, groundwater recharge may decrease [87] and be less available for human needs. Concomitantly, more intense rainfall and land use changes towards annual crops or trees without understorey may increase runoff and decrease water travel times downstream, thereby reducing the filtration process of pathogens before entering the stream.…”
Section: Discussionmentioning
confidence: 99%
“…See Neitsch et al (2009) -The soil map (Chaplot et al, 2005;Valentin et al, 2008b) with associated soil properties (Shrestha et al, 2013). -The 2012 land use map from de Rouw et al (2015) and Lacombe et al (2016) with associated management practices: forest and teak plantations with mature trees at the beginning of the simulation, simplified management operations for crops. Fertilization through grazing was used to introduce E. coli bacteria into the system.…”
Section: The Swat Model Setup and Input Parametersmentioning
confidence: 98%
“…The simulated annual average of the contribution of surface runoff to stream flow was about 45% whereas the groundwater (lateral flow and shallow aquifer) contribution was 55%. The hydrological response of the Houay Pano headwater catchment is known to be very sensitive to land use (Lacombe et al, 2016), which determines the infiltration and runoff rates. The high contribution of both lateral flow and the shallow aquifer may be related to the high infiltration rates in fallow and forest land uses together with run-off/run-on processes and soil crusted areas across the catchment (Patin et al, 2012;Ribolzi et al, 2011b;Ziegler et al, 2004).…”
Section: Stream Discharge Calibrationmentioning
confidence: 99%
“…5) showed that the observed precipitation in the study area did not decrease significantly from 1960 to 2009, while the annual streamflow (except region 3) and the runoff coefficients decreased significantly (P < 0.05) under this meteorological condition. This discrepancy could be attributed mostly to LUCC (Lacombe et al, 2008(Lacombe et al, , 2016. In order to analyze the impact of LUCC on the streamflow, the land use data for 1980 and 2005 were used in the validated SWAT model and the DEM, and the soil data remained constant.…”
Section: Impact Of the Observed Lucc On Streamflowmentioning
confidence: 99%
“…Some researchers have indicated that tree planting has both negative and positive effects on water resources and that the overall effect was the result of a balance between them, which was strongly dependent on tree density (Tobella et al, 2014). Lacombe et al (2016) found that soil infiltrability was an important factor in explaining how two modes of afforestation (natural regeneration vs. planting) led to opposite changes in the streamflow regime. Huang (1982) analyzed Soviet research results and found that 48 % of runoff coefficients increased, 32 % had no change, and 20 % decreased with a watershed forest increase.…”
mentioning
confidence: 99%